214k views
3 votes
Need this badly!!!!!!

Need this badly!!!!!!-example-1
User Rzlines
by
5.7k points

1 Answer

5 votes

Hello!

The answer is:

The center of the circle is located on the point (-9,-2) and the radius is 6 units.

Why?

To solve the problem, we need to use the given equation which is in the general form.

We are given the circle:


x^(2)+y^(2)+18x+4y+49=0

We know that a circle can be written in the following form:


(x-h)^(2)+(y-k)^(2)=r^(2)

Where,

h is the x-coordinate of the center of the circle

k is the y-coordinate of the center of the circle

r is the radius of the circle.

So, to find the center and the radius, we need to perform the following steps:

- Moving the constant to the other side of the equation:


x^(2)+y^(2)+18x+4y=-49

- Grouping the terms:


x^(2)+18x+y^(2)+4y=-49

- Completing squares for both variables, we have:

We need to sum to each side of the equation the following term:


((b)/(2))^(2)

Where, b, for this case, will the coefficients for both terms that have linear variables (x and y)

So, the variable "x", we have:


x^(2) +18x

Where,


b=18

Then,


((18)/(2))^(2)=(9)^(2)=81

So, we need to add the number 81 to each side of the circle equation.

Now, for the variable "y", we have:


y^(2) +4y

Where,


b=4


((4)/(2))^(2)=(2)^(2)=4

So, we need to add the number 4 to each side of the circle equation.

Therefore, we have:


(x^(2)+18x+81)+(y^(2)+4y+4)=-49+81+4

Then, factoring, we have that the expression will be:


(x+9)^(2)+(y+2)^(2)=36

- Writing the standard form of the circle:

Now, from the simplified expression (after factoring), we can find the equation of the circle in the standard form:


(x+9)^(2)+(y+2)^(2)=36

Is also equal to:


(x-(-9))^(2)+(y-(-2))^(2)=36

Where,


h=-9\\k=-2\\r=√(36)=6

Hence, the center of the circle is located on the point (-9,-2) and the radius is 6 units.

Have a nice day!